Kinerja Alat Pengeringan Kopra Sistem Oven Skala Kelompok Tani dan Karakteristik Produk / Performance of Copra Drying Oven System of Farmer Scale and Product Characteristics - A. Lay; Ismail Maskromo (Buletin Palma, 2016)
Traditional copra processing by smoking and sun drying methods will produce low quality copraand oil. In order to improve the quality of copra and oil, copra drier through oven system with controlled drying temperature is a necessity. The purpose of this research is to design a copra dryer through oven system that can be utilized by farmer groups. Research carried out from May 2014 to December 2015, with tool’s construction and field test conducted at the Repair Engineering and Laboratory Equipment of Indonesian Palm Crops Research Institute. Moreover, copra and oil’s quality analysis performed at Research and Standardization of Industrial Institute Laboratory, Manado. The quality analysis is based on valid quality standard. The research results showed that copra drier system on a farmers scale, using coconut coir as a fuel, has been built with capacity of 1550-1650 coconuts/process period. Drying temperature is varied between 28-70 Cwith optimum temperature at 55-60 C and drying time approximately 27 hours.It produces various copra such as, white copra, brown copra and dark copra, with water content of 4.36-4.88%, fat content of 63.53-64.17% and Free Fatty Acid of 0.05-0.12%. White copra, which then processed into frying oil, produced white color oil with water content of 0.05%, peroxide value 0.13 meq O2/kg without any lead (Pb) detected in the oil. As a result, coconut oil can be safely consumed without any purification process. In conclusion, copra drying through oven system is sufficient enough to apply for farmers group in order to encourage excellent quality copra and oil processing.ABSTRAKPengolahan kopra secara tradisional dengan cara pengasapan dan penyinaran matahari  menghasilkan kopra dan minyak bermutu rendah. Untuk meningkatkan mutu kopra dan minyak diperlukan alat pengeringan kopra sistem oven dengan suhu pengeringan terkontrol. Penelitian bertujuan untuk merancang alat pengering kopra  sistem oven yang dapat diaplikasikan pada kelompok tani. Penelitian dilaksanakan pada bulan Mei 2014 sampai Desember 2015, perancangan alat dan uji lapang dilakukan di Bengkel Rekayasa Alat Balai Penelitian Tanaman Palma, analisis mutu kopra dan minyak kelapa di Laboratorium  Balai Riset dan Standardisasi Industri Manado. Hasil penelitian menun-jukkan bahwa telah dirancang alat  pengering  kopra sistem oven skala kelompok tani, yang menggunakan bahan bakar sabut kelapa, kapasitas olah 1550-1650 butir kelapa/periode proses.  Pengeringan kopra dengan suhu pengeringan  bervariasi 28-70ºC, suhu optimal 55-60ºC, waktu pengeringan 27 jam,  dihasilkan  kopra beragam, yakni kopra putih,  kopra coklat, dan kopra gelap,  kadar air 4,36-4,88%, kadar lemak 63,53-64,17% dan kadar ALB 0,05-0,12%. Kopra putih yang diolah menjadi minyak kelapa, menghasilkan minyak kelapa berwarna putih, kadar air 0,05%, bilangan peroksida 0,13 meq O2/kg, dan tidak terdeteksi cemaran logam timbal (Pb). Minyak kelapa yang dihasilkan dapat dikonsumsi sebagai minyak goreng walaupun tanpa proses pemurnian. Alat pengeringan kopra sistem oven, cukup memadai untuk diaplikasikan pada kelompok tani dalam menunjang pengolahan kopra dan minyak bermutu baik.